The Relationship Between Ventilation And Household Crowding With The Incidence Of Acute Respiratory Infections In Children Under Five - Riana Dewi; Zulaikha Agustinawati; Ike Sri Wahyuni; Siti Chodijah; Bulan Purnamasari (Citra Delima Scientific journal of Citra Internasional Institute, 2026)
The incidence of Acute Respiratory Infections (ARI) among children under five at the Punti Kayu Public Health Center in Palembang remains high. Risk factors leading to ARI in this age group include severe complications that can result in mortality. In 2024, the prevalence of ARI reached 58.8%. Over the last three years, the number of ARI cases among children aged one to four years has steadily increased, with 47 cases recorded in 2022, 53 cases in 2023, and 64 cases in 2024. This research utilized a quantitative design with a cross-sectional approach. The study population comprised all parents of children under five who visited the Punti Kayu Public Health Center Palembang for treatment in 2024, totaling 255 respondents, with a sample size of 72 children under five. Statistical analysis was performed using the Chi-Square test and logistic regression. Results The statistical analysis revealed a significant relationship (p-value < 0.05) between the independent variables and the incidence of ARI. Specifically, both residential density (p-value = 0.00), and ventilation (p-value = 0.00) were significantly associated with ARI incidence. Conclusion This study concludes that there is a significant relationship between household crowding, ventilation, and the incidence of ARI in children under five.